ASSESSMENT OF CONCENTRATION STATUS OF SOME HEAVY METALS IN WATER ALONG RIVER DILIMI, JOS NORTH, PLATEAU STATE-NIGERIA - Ezekiel Oiganji; K. I. Dikam (Universitas Trisakti, 2020)
Aim: This study was carried out to assess concentration status of someheavy metals in water along River Dilimi, Nigeria. The Nigerian inland waterbodies have been subjected to various forms of degradation due topollution. River Dilimi in Jos North of Plateau state capital is one of suchendangered inland water bodies. Activities around and in the river has ledto discharge of various heavy metal pollutants into the aquaticenvironment rendering water unsuitable for its intended purposes.Methodology and Results: Six (6) water samples were collected at theupper, centre and lower section of the river at the 20 and 120 cm depth, for every six (6) weeks making a total of eighteen (18) samples, Analyzed atNigerian Institute of Mining and Geosciences, Jos. The water samplescollected were pre-treated with few drops of concentrated Nitric acid, anddigested with Aqua-regia in the ratio of 3:1 for an hour. Different standardsolutions were prepared for AAS analysis under Beer-Lambert method ofmetal analysis using Atomic Absorption Spectrophotometer (AAS). Thedata obtained were subjected statistical analysis. The results obtained fromanalyzed water samples were alarming, iron, lead, cadmium andManganese were above the recommended threshold by 277, 6,400, 1,233and 580% accordingly, while zinc and copper were within permissible limit.Conclusion, significance and impact study: River Dilimi can be said to behighly concentrated with hazardous metals of concern like Fe, Pb, Cd andMn. This as a result of bioaccumulation will affect human and animalhealth, aquatic life and crop productivity.